ANALISA TURUNNYA KUALITAS STERILISASI PADA ULTRAVIOLET WATER STERILIZER DI MT. DRAGONARIA DENGAN METODE FAULT TREE ANALYSIS - Aditya Arin Sasongko; Abdi Seno; Andy Wahyu Hermanto (Dinamika Bahari, 2017)
Ultraviolet water sterilizer is a long cylindrical device used for the sterilization of water into drinkable water. Ultraviolet water sterilizer has two main parts: an adapter and UV tubes. The adapter serves to drain ration electricity in accordance with the voltage and current required by ultraviolet water sterilizer. Tubes UV is containing lamps germicides where light is equipment major unruk make the water drinkable and the water will flow along the ultraviolet rays, so that the water flowing in the tube is passed through the sterilization process with ultraviolet rays so that the water unfit for consumption. The problems that the authors take in this study are the factors that affect the declining quality of sterilization, the impact of what happens when the quality of sterilization decreased, and what efforts made to keep the quality of sterilization is not decreased. The method used is the method of fault tree analysis, a method to find the root of the problem by using a fault tree and simple logic gates to help determine the basic problem. Fault tree analysis method consists of a top event, intermediate event, and basic event where all three events are interrelated to form the fault tree that can be seen cause and effect. Data collected through observation, interviews, and literature directly to the subject related to the factors, the impact, as well as the efforts of the decline in the sterilization process to the sterilizer in order to improve the quality of drinking water. The cause of the decline to the sterilizer sterilization process in order to improve the quality of drinking water in MT. Dragonaria that dirty filters, dirty water tubes, and the dirty germicidal lamp or berdampaknya resulting in less fresh water, complaint against the company, as well as the ship operational cost is reduced. Therefore made some efforts to improve the quality of the results of sterilization including cleaning filters, cleaning water tubes, and also clean the germicidal lamp, as well as auxiliary engine checks periodically so that the quality of sterilization can be increased.